A method for regenerating waste nickel-cobalt-manganese ternary positive electrode material into lithium-rich manganese-based positive electrode material
Patent Information
- Application Number
- CN202610890913.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明的目的在于提供一种废旧镍钴锰三元正极材料再生为富锂锰基正极材料的方法,以解决现有回收方法流程复杂,使用大量昂贵且有害有机试剂,污染严重;产出的回收材料降级,无法直接再生为高比能正极材料,且耗能高等技术问题
[0024] 1. The pretreatment process is simple and efficient. This invention uses an oxidizing solution to pretreat waste nickel-cobalt-manganese ternary cathode materials, which can effectively open the manganese ion diffusion channels, allowing the manganese source to migrate into the material more quickly.
Smart Images

Figure CN122916233A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of waste lithium-ion battery recycling technology, specifically relating to a method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material. Background Technology
[0002] Since the commercialization of lithium-ion batteries (LIBs) in 1991, they have completely replaced traditional nickel-metal hydride / nickel-cadmium batteries, becoming the preferred energy storage technology for everything from portable electronic devices to electric vehicles, thanks to their core advantages such as high energy density, long cycle life, and low self-discharge rate. With the explosive growth of the global new energy industry, the lithium-ion battery market continues to expand, maintaining the highest compound annual growth rate among all types of rechargeable batteries.
[0003] Among various lithium-ion battery systems, nickel-cobalt-manganese (NCM) ternary materials have become the mainstream cathode material for power batteries due to their combination of the structural stability of LiCoO2, the high specific capacity of LiNiO2, and the cost advantage of LiMnO2. However, power batteries generally have a service life of less than 10 years and are about to face a large-scale wave of scrapping. According to industry statistics, the cumulative amount of retired power batteries in my country exceeded 500,000 tons in 2022 and is expected to exceed 1.2 million tons in 2025. Waste ternary cathode batteries are rich in high-value metals (nickel, cobalt, manganese, and lithium) and toxic components (fluorides, organic electrolytes). Improper disposal will lead to environmental risks such as heavy metal pollution and leakage of electrolyte decomposition products, while also causing a serious waste of strategic metal resources.
[0004] Patent CN202010977913.4 discloses a method for recycling ternary lithium battery cathode materials. The method involves: a) taking lithium battery cathode powder and leaching it in an inorganic acid without a reducing agent to obtain an acid leaching solution; b) adjusting the pH value of the acid leaching solution and using P227 as an extractant to perform co-extraction on nickel, cobalt, and manganese, while simultaneously separating lithium; c) back-extracting the co-extracted organic phase loaded with nickel, cobalt, and manganese using acid to obtain a back-extracting solution, and then adding oxalic acid as a co-precipitant to precipitate nickel, cobalt, and manganese ions in the back-extracting solution to prepare a nickel-cobalt-manganese precursor; d) calcining the prepared nickel-cobalt-manganese precursor in a high-temperature environment to finally obtain a powdered lithium battery cathode material. Patent CN202210554762.0 discloses a green recycling process for preparing battery-grade cobalt suboxide from waste ternary cathode materials. The process consists of: a) Pretreatment: After crushing the waste ternary cathode materials, a high-purity cobalt solution is obtained through acid leaching, purification, and extraction; b) Coprecipitation reaction: The high-purity cobalt solution and sodium carbonate solution are pumped into a reaction vessel in a precise ratio, and a controlled coprecipitation reaction is carried out under heating and additive control to generate a high-purity cobalt carbonate precursor; c) Washing and dehydration: The cobalt carbonate slurry is centrifuged and deeply washed with deionized water to ensure that the sodium ion content meets the standard; d) Drying and calcination: The cobalt carbonate is treated with flash drying technology and then reduced and calcined to obtain high-purity cobalt suboxide powder.
[0005] The methods described above can all be used to recycle and reuse waste ternary materials. However, these recycling technologies mainly focus on hydrometallurgy (acid leaching-extraction) or pyrometallurgy, which have a series of problems such as complex processes, expensive organic reagents, material degradation after recycling, and pollution generated during the recycling process. Summary of the Invention
[0006] The purpose of this invention is to provide a method for regenerating waste nickel-cobalt-manganese ternary cathode materials into lithium-rich manganese-based cathode materials, in order to solve the technical problems of existing recycling methods, such as complex processes, use of large amounts of expensive and harmful organic reagents, serious pollution, downgraded recycled materials that cannot be directly regenerated into high-energy-density cathode materials, and high energy consumption.
[0007] A method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material includes the following steps:
[0008] S1. Powder samples of waste nickel-cobalt-manganese ternary cathode material were obtained by dismantling waste batteries.
[0009] S2. Add the oxidizing solution to the powder sample and heat and stir.
[0010] S3. Filter, wash, and dry the powder sample;
[0011] S4. Add manganese source to the dried powder sample, mix evenly, then perform the first sintering step, cool, and generate lithium-rich manganese-based cathode material precursor.
[0012] S5. Add the lithium source to the lithium-rich manganese-based cathode material precursor, mix thoroughly, then perform the second sintering step, cool, sieve, and grind to obtain the lithium-rich manganese-based cathode material xLiTMO2·(1-x)Li2MnO3, where x is 0.4-0.6. LiTMO2TM is LiNi a Co b Mn c O 22 The transition metal elements, a+b+c=1, and the specific values of a, b, and c are related to the proportions of Ni, Co, and Mn in the waste nickel-cobalt-manganese ternary cathode material.
[0013] The amount of lithium and manganese sources added here is calculated based on the x value in the final lithium-rich manganese-based cathode material xLiTMO2·(1-x)Li2MnO3.
[0014] Further, in step S2, the oxidizing solution is one of K2S2O8 solution, hydrogen peroxide, or (NH4)2S2O8 solution.
[0015] Further, in step S2, the concentration of the oxidizing solution is 0.1 mol / L to 0.3 mol / L.
[0016] Further, in step S2, the solid-liquid mass ratio of the oxidizing solution and the powder sample is 1 / 200-1 / 50.
[0017] Further, in step S3, the powder sample is washed with water 3-5 times, then filtered and washed with an organic solvent, and dried at 50℃-100℃ for 3-6 hours. The organic solvent is acetonitrile or ethanol.
[0018] Further, in step S4, the manganese source is at least one of MnCO3, MnSO4 and Mn(OH)2.
[0019] Furthermore, in step S4, the temperature of the first sintering step is 400℃-600℃, the holding time is 5h-7h, and the sintering atmosphere is an oxidizing atmosphere.
[0020] Further, in step S5, the lithium source is at least one of LiOH, LiNO3, and Li2CO3.
[0021] Further, in step S5, the sintering temperature in the second step is 850℃-950℃, the holding time is 11h-13h, and the sintering atmosphere is an oxidizing atmosphere. The oxidizing atmosphere in the first and second sintering steps is air or oxygen.
[0022] Furthermore, the heating rates for the first and second sintering steps are 5°C / min and 10°C / min, respectively.
[0023] Compared with existing technologies, the beneficial effects of the method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material provided by this invention are:
[0024] 1. The pretreatment process is simple and efficient. This invention uses an oxidizing solution to pretreat waste nickel-cobalt-manganese ternary cathode materials, which can effectively open the manganese ion diffusion channels, allowing the manganese source to migrate into the material more quickly.
[0025] 2. Simple process, environmentally friendly, and economically efficient. This invention uses a two-stage calcination process to directly regenerate waste nickel-cobalt-manganese ternary cathode materials into high-performance lithium-rich manganese cathode materials by supplementing them with lithium and manganese sources. Compared to traditional hydrometallurgical processes (acid leaching-extraction) or pyrometallurgical processes that suffer from material degradation, this invention can directly obtain high-energy-density cathode materials, reducing recycling energy consumption and resulting in cleaner and less polluting processes.
[0026] 3. Synergistic segmented heating process for structural repair and morphology control. This invention innovatively adopts a stepwise sintering strategy of "manganese supplementation in the first sintering and lithium supplementation in the second sintering". This strategy prioritizes the migration and solid solution of manganese, and then adds lithium source, which effectively optimizes the uniformity of the bulk phase structure of the recycled material, and finally successfully synthesizes particles with good crystallinity and uniform dispersion.
[0027] In summary, this invention provides a direct regeneration method that integrates direct regeneration and size and morphology control, offering an effective technical path for the green and high-value utilization of retired lithium-ion battery nickel-cobalt-manganese ternary cathode materials. Attached Figure Description
[0028] Figure 1 Comparison of XRD spectra of the lithium-rich manganese cathode active material obtained by regeneration in Example 1 of this invention;
[0029] Figure 2 Comparison of XRD spectra of the lithium-rich manganese cathode active material obtained by regeneration in Comparative Example 1 of this invention;
[0030] Figure 3 This is a SEM image of the lithium-rich manganese cathode active material obtained by regeneration in Example 1 of the present invention;
[0031] Figure 4 This is a SEM image of the lithium-rich manganese cathode active material obtained by regeneration in Example 2 of the present invention;
[0032] Figure 5 The first charge-discharge curves of the assembled batteries in Example 1 and Comparative Examples 1-7 of this invention are shown. Detailed Implementation
[0033] The present invention will be further described below with reference to specific embodiments, but is not limited to these specific embodiments. Unless otherwise specified, all ratios in the embodiments of the present invention are mass ratios.
[0034] Unless otherwise specified, the experimental methods described in the following examples are conventional methods; unless otherwise specified, the reagents and materials are commercially available.
[0035] Example 1
[0036] A method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material includes the following steps:
[0037] S1. Take out the waste nickel-cobalt-manganese ternary cathode material (the atomic percentage of nickel in the three transition metals was determined to be 51.2%, cobalt to be 19.4%, and manganese to be 29.4% by ICP-OES) and sieve it through a 300-mesh sieve to obtain a powder sample.
[0038] S2. Add 0.1 mol / L K2S2O8 solution to the powder sample, control the solid-liquid mass ratio to 1:100, and then place it on a 70℃ heating and stirring table at 200 r / min for 3 h.
[0039] S3. The powder sample is filtered and washed, washed 3 times with deionized water, and then washed once with acetonitrile. After taking out the sample, it is transferred to a water-heated oven and dried at 95°C for 4 hours.
[0040] S4. Calculate the amount of manganese carbonate and lithium carbonate according to x=0.5. Add MnCO3 to the dried powder sample, pre-grind it in a mortar for 10 min, then put it into a ball mill at a speed of 600 r / min for 6 h to mix it evenly. Then put it into a muffle furnace for the first step of sintering in an air atmosphere at a sintering temperature of 500℃, a holding time of 6 h, and a heating rate of 5℃ / min. Then cool it in the furnace to generate a lithium-rich manganese-based cathode material precursor.
[0041] S5. Li₂CO₃ was added to the lithium-rich manganese-based cathode material precursor, ground in a mortar for 1 hour, and then mixed evenly. The mixture was then placed in a tube furnace for the second sintering step, held at 920℃ for 12 hours in an oxygen atmosphere with a heating rate of 5℃ / min, and cooled in the oxygen atmosphere within the furnace. The sample was then sieved through a 400-mesh sieve to finally regenerate the lithium-rich manganese-based cathode material 0.5LiNi. 0.512 Co 0.194 Mn 0.294 O2·0.5Li2MnO3.
[0042] Example 2
[0043] The difference between this embodiment and Embodiment 1 is that the oxidizing solution used in step S2 is a 0.2 mol / L K2S2O8 solution, and the solid-liquid mass ratio is controlled at 1:50. The rest is the same as in Embodiment 1.
[0044] Example 3
[0045] The difference between this embodiment and Embodiment 1 is that the oxidizing solution used in step S2 is a 0.3 mol / L K2S2O8 solution, and the solid-liquid mass ratio is controlled at 1:200. Everything else is the same as in Embodiment 1.
[0046] Example 4
[0047] The difference between this embodiment and Embodiment 1 is that the oxidizing solution used in step S2 is a 0.3 mol / L H2O2 solution, and the solid-liquid mass ratio is controlled at 1:200. The rest is the same as in Embodiment 1.
[0048] Example 5
[0049] The difference between this embodiment and Embodiment 1 is that the oxidizing solution used in step S2 is a 0.1 mol / L (NH4)2S2O8 solution, and the solid-liquid mass ratio is controlled at 1:100. Everything else is the same as in Embodiment 1.
[0050] Example 6
[0051] The difference between this embodiment and Embodiment 1 is that in steps S4 and S5, the sintering temperature of the first step is 400°C and the sintering temperature of the second step is 850°C. The rest are the same as in Embodiment 1.
[0052] Example 7
[0053] The difference between this embodiment and Embodiment 1 is that in steps S4 and S5, the sintering temperature of the first step is 600°C and the sintering temperature of the second step is 950°C. The rest are the same as in Embodiment 1.
[0054] Example 8
[0055] The difference between this embodiment and embodiment 1 is that in steps S4 and S5, the first sintering holding time is 5 hours and the second holding time is 11 hours. The rest is the same as in embodiment 1.
[0056] Example 9
[0057] The difference between this embodiment and embodiment 1 is that in steps S4 and S5, the first sintering holding time is 7 hours and the second holding time is 13 hours. The rest is the same as in embodiment 1.
[0058] Example 10
[0059] The difference between this embodiment and embodiment 1 is that in step S4, the sintering temperature of the first sintering step is 400℃ and the holding time is 5h; in the first sintering step and the second sintering step, the heating rate is 7℃ / min, and the rest is the same as in embodiment 1.
[0060] Example 11
[0061] The difference between this embodiment and embodiment 1 is that in step S5, the sintering temperature of the second sintering step is 850℃ and the holding time is 11h; in the first and second sintering steps, the heating rate is 10℃ / min, and the rest is the same as in embodiment 1.
[0062] Example 12
[0063] The difference between this embodiment and Embodiment 1 is that in step S4, the manganese source is MnSO4, while the rest is the same as in Embodiment 1.
[0064] Example 13
[0065] The difference between this embodiment and Embodiment 1 is that in step S4, the manganese source is Mn(OH)2, while the rest is the same as in Embodiment 1.
[0066] Example 14
[0067] The difference between this embodiment and Embodiment 1 is that in step S5, the lithium source is LiOH, while the rest is the same as in Embodiment 1.
[0068] Example 15
[0069] The difference between this embodiment and Embodiment 1 is that in step S5, the lithium source is LiNO3, while the rest is the same as in Embodiment 1.
[0070] Example 16
[0071] The difference between this embodiment and Embodiment 1 is that in steps S4 and S5, the manganese source is Mn(OH)2, the first sintering temperature is 400℃, the second sintering temperature is 950℃, and the rest is the same as in Embodiment 1.
[0072] Example 17
[0073] The difference between this embodiment and Embodiment 1 is that in steps S4 and S5, the manganese source is MnSO4, the first sintering temperature is 400℃, the second sintering temperature is 950℃, and the rest is the same as in Embodiment 1.
[0074] Example 18
[0075] The difference between this embodiment and Embodiment 1 is that in steps S4 and S5, the first sintering temperature is 600°C and the lithium source is LiOH, and the second sintering temperature is 850°C. The rest is the same as in Embodiment 1.
[0076] Example 19
[0077] The difference between this embodiment and Embodiment 1 is that in steps S4 and S5, the first sintering temperature is 600°C and the lithium source is LiNO3, and the second sintering temperature is 850°C. The rest is the same as in Embodiment 1.
[0078] Example 20
[0079] The difference between this embodiment and Embodiment 1 is that in steps S4 and S5, the amounts of manganese carbonate and lithium carbonate are calculated according to x=0.4, ultimately yielding the lithium-rich manganese-based cathode material 0.4LiNi. 0.512 Co 0.194 Mn 0.294 O2·0.6Li2MnO3, the rest is the same as in Example 1.
[0080] Example 21
[0081] The difference between this embodiment and Embodiment 1 is that in steps S4 and S5, the amounts of manganese carbonate and lithium carbonate are calculated according to x=0.4, ultimately yielding the lithium-rich manganese-based cathode material 0.6LiNi. 0.512 Co 0.194 Mn 0.294 O2·0.4Li2MnO3, the rest is the same as in Example 1.
[0082] Comparative Example 1
[0083] The difference between this comparative example and Example 1 is that step S2 is removed and the powder sample is not treated with an oxidizing solution; otherwise, it is the same as Example 1.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 1 is that, after step S3, manganese source and lithium source are added to the dried powder sample simultaneously, and one-step sintering is carried out under an oxygen atmosphere. The sintering temperature is 920℃, the holding time is 20h, and the heating rate is 5℃ / min. The rest is the same as in Example 1.
[0086] Comparative Example 3
[0087] The difference between this comparative example and Example 1 is that in step S4, after adding the lithium source, the first sintering is performed, and after adding the manganese source, the second sintering is performed. The rest is the same as in Example 1.
[0088] Comparative Example 4
[0089] The difference between this comparative example and Example 1 is that in steps S4 and S5, the amounts of manganese carbonate and lithium carbonate were calculated according to x=0.3, ultimately yielding the lithium-rich manganese-based cathode material 0.3LiNi. 0.512 Co 0.194 Mn 0.294 O2·0.7Li2MnO3, the rest is the same as in Example 1.
[0090] Comparative Example 5
[0091] The difference between this comparative example and Example 1 is that in steps S4 and S5, the amounts of manganese carbonate and lithium carbonate were calculated according to x=0.7, ultimately yielding the lithium-rich manganese-based cathode material 0.7LiNi. 0.512 Co 0.194 Mn 0.294 O2·0.3Li2MnO3, the rest is the same as in Example 1.
[0092] Comparative Example 6
[0093] The difference between this comparative example and Example 1 is that the oxidizing solution used in step S2 is a 0.4 mol / L K2S2O8 solution, the solid-liquid mass ratio is controlled at 1:250, and the sintering conditions are: the first step sintering temperature is 400℃ and sintering time is 4 hours, and the second step sintering temperature is 920℃ and sintering time is 10 hours.
[0094] Comparative Example 7
[0095] The difference between this comparative example and Example 6 is that the oxidizing solution used in step S2 is a 0.4 mol / L K2S2O8 solution, and the solid-liquid mass ratio is controlled at 1:20. The rest is the same as that of Comparative Example 6.
[0096] Electrochemical performance testing: The cathode materials obtained in Examples 1-21 and Comparative Examples 1-7 were used to assemble batteries according to the following steps, and the following electrochemical performance tests were conducted, corresponding to Examples 1-21 and Comparative Examples 1-7. The obtained recycled ternary cathode active material, carbon black, and binder (PVDF) were mixed at a mass ratio of 8:1:1 to form a slurry. The slurry was uniformly coated onto a carbon-coated aluminum foil current collector, dried in an 80°C forced-air oven, and then vacuum-dried at 120°C for 6 hours to form a cathode sheet. Using a lithium sheet as the counter electrode and a PP separator (Celgard 2500), an appropriate amount of electrolyte (1M LiPF6 dissolved in an organic solvent with a volume ratio of EC:DMC = 3:7) was added, and 2032 coin cells were assembled in a glove box under argon protection.
[0097] Table 1. Preparation parameters for each example and comparative example.
[0098]
[0099]
[0100] Table 2 Structural parameters and electrochemical performance of each embodiment and comparative example
[0101] Sample Name 0.1C first-cycle discharge specific capacity First lap Coulomb efficiency 1C First-Cycle Discharge Specific Capacity 1C100-cycle capacity retention Example 1 277.6 81.5% 196.5 91.4% Example 2 265.8 82.6% 190.2 89.8% Example 3 268.4 81.2% 187.5 87.3% Example 4 262.1 81.8% 193.4 88.6% Example 5 264.5 82.3% 195.8 89.2% Example 6 259.7 81.5% 190.8 88.1% Example 7 268.4 83.1% 189.6 90.5% Example 8 265.2 80.8% 186.1 86.5% Example 9 269.1 82.9% 190.3 90.1% Example 10 261.3 81.9% 192.6 88.8% Example 11 254.8 80.5% 185.7 86.2% Example 12 263.7 82.1% 194.9 88.9% Example 13 266.2 82.7% 195.5 89.6% Example 14 260.5 81.6% 191.8 88.3% Example 15 267.8 81.0% 188.9 87.6% Example 16 268.6 79.5% 189.2 84.8% Example 17 263.4 80.6% 194.5 86.8% Example 18 268.9 81.3% 190.1 87.9% Example 19 266.1 80.9% 191.3 87.2% Example 20 262.4 80.2% 188.5 86.6% Example 21 264.6 81.2% 190.2 87.4% Comparative Example 1 205.3 68.7% 156.5 65.7% Comparative Example 2 208.4 66.6% 155.2 71.6% Comparative Example 3 245.7 71.2% 171.6 66.2% Comparative Example 4 234.5 72.2% 164.8 72.4% Comparative Example 5 233.2 71.0% 161.2 75.1% Comparative Example 6 229.4 68.7% 158.2 78.6% Comparative Example 7 236.7 70.9% 162.5 77.3%
[0102] The experimental parameters for each example in this study are shown in Table 1.
[0103] Initial charge-discharge performance, measured by initial charge-discharge voltage and specific capacity at 0.1C. Charge-discharge cycle stability was assessed by first activating the system with three cycles at 0.05C, followed by 100 cycles at 1C. The results are shown in Table 2.
[0104] Figure 1 and Figure 2 The XRD patterns of the lithium-rich manganese materials obtained in Example 1 and Comparative Example 1 are shown respectively. The XRD pattern of the regenerated cathode material exhibits good characteristic peaks typical of lithium-rich manganese materials, belonging to the typical R-3m and C2 / m composite crystal structure. There are no impurity peaks, and all peaks are sharp, indicating good crystallinity. The sharp peaks also indicate good crystallinity. The significant splitting of the 006 / 102 and 108 / 110 peaks indicates a perfect, highly ordered layered structure of lithium-rich manganese materials. In contrast, the material in Comparative Example 2 shows obvious diffraction peak splitting. This is because the sample without oxidizing solution treatment has difficulty in manganese ion diffusion during sintering, resulting in the incomplete fusion of the generated Li2MnO3 and LiTMO2 phases.
[0105] Figure 3 and Figure 4 The images show SEM images of the lithium-rich manganese materials obtained in Example 1 and Comparative Example 2, respectively. It can be seen from the images that the materials formed uniformly dispersed single crystal particles of about 100 nanometers in size, with regular shapes and good crystallinity. However, the sample of Comparative Example 2 showed an irregular morphology, with severe particle adhesion and uneven size. This is because the high-temperature sintering in one step made the grain growth and grain boundary fusion process too fast, and the lithium and manganese diffusion was insufficient, resulting in a reaction at the grain boundary.
[0106] Figure 5The table shows the 0.1C first-cycle charge-discharge curves of the coin cells assembled in Example 1 and Comparative Examples 1-7. Comparing Example 1 with Comparative Example 1, it can be seen that the strategy of adding the manganese source first and then the lithium source significantly improves the performance of the sample compared to ordinary materials without K2S2O8 solution pretreatment, achieving a reversible capacity of 277.6 mAh / g. In contrast, the Comparative Example 1 sample exhibits poor kinetics, with difficulty in ion insertion / extraction during charge and discharge, resulting in a first-cycle reversible capacity of only 205.3 mAh / g. Comparing Example 1 with Comparative Example 2, it can be seen that stepwise sintering improves the integrity and regularity of the morphological structure; therefore, combined with the performance data in Table 2, it can be seen that both reversible capacity and cycle stability are improved. Comparing Example 1 with Comparative Example 3, it can be seen that the performance of simultaneous addition of manganese and lithium sources in a single-step sintering step is poor, with a reversible capacity of only 245.7 mAh / g. This is because adding the manganese source first facilitates the diffusion of manganese. A comparison of Example 1 with Comparative Examples 4 and 5 shows that when x exceeds 0.4-0.6, the Li2MnO3 phase and the LiTMO2 phase do not fuse sufficiently, resulting in a decrease in capacity. A comparison of Example 1 with Comparative Examples 6 and 7 shows that the solid-liquid ratio during oxidizing solution pretreatment affects the oxidation effect of the particles. An excessively low solid-liquid ratio easily leads to insufficient particle oxidation, while an excessively high solid-liquid ratio easily causes over-oxidation of the particles; therefore, the product performance of both types of particles decreases significantly.
[0107] This invention employs an oxidizing solution to pretreat waste ternary materials, followed by a two-step sintering strategy of first adding a manganese source and then a lithium source. This successfully constructs a second phase of Li2MnO3 within the layered structure of the original ternary material's LiTMO2, thereby directly realizing the regeneration and conversion from waste ternary materials into lithium-rich manganese-based cathode materials.
[0108] This invention directly regenerates waste nickel-cobalt-manganese ternary cathode materials into high-capacity lithium-rich manganese cathode materials. The process is simplified, with minimal reagent pollution. Furthermore, potassium persulfate solution is used for pretreatment to improve the electrochemical performance of the recycled materials. This invention has low equipment requirements and is suitable for industrial-scale ternary lithium battery recycling and regeneration operations.
[0109] The above detailed description is a specific illustration of one feasible embodiment of the present invention, and this embodiment is not intended to limit the scope of patent protection of the present invention. All equivalent implementations or modifications made without departing from the spirit of the present invention should be covered within the scope of the technical solution of the present invention.
Claims
1. A method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material, characterized in that, Includes the following steps: S1. After disassembling the waste battery, a powder sample of the waste nickel-cobalt-manganese ternary cathode material was obtained. S2. Add the oxidizing solution to the powder sample and heat and stir. S3. Filter, wash, and dry the powder sample; S4. Add manganese source to the dried powder sample, mix evenly, then perform the first sintering step, cool, and generate lithium-rich manganese-based cathode material precursor. S5. Add the lithium source to the lithium-rich manganese-based cathode material precursor, mix evenly, and then perform the second step of sintering, cooling, sieving, and grinding to obtain the lithium-rich manganese-based cathode material xLiTMO2·(1-x)Li2MnO3, where x is 0.4-0.
6.
2. The method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material as described in claim 1, characterized in that, In step S2, the oxidizing solution is one of K2S2O8 solution, hydrogen peroxide, or (NH4)2S2O8 solution.
3. The method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material as described in claim 2, characterized in that, In step S2, the concentration of the oxidizing solution is 0.1 mol / L to 0.3 mol / L.
4. The method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material as described in claim 2, characterized in that, In step S2, the solid-liquid mass ratio of the oxidizing solution and the powder sample is 1 / 200-1 / 50.
5. The method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material as described in claim 1, characterized in that, In step S3, the powder sample is washed with water 3-5 times, then washed with organic solvent by vacuum filtration, and dried at 50℃-100℃ for 3-6 hours.
6. The method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material as described in claim 1, characterized in that, In step S4, the manganese source is at least one of MnCO3, MnSO4 and Mn(OH)2.
7. The method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material as described in claim 1, characterized in that, In step S4, the temperature of the first sintering step is 400℃-600℃, the holding time is 5h-7h, and the sintering atmosphere is an oxidizing atmosphere.
8. The method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material as described in claim 1, characterized in that, In step S5, the lithium source is at least one of LiOH, LiNO3, and Li2CO3.
9. The method for regenerating waste nickel-cobalt-manganese ternary cathode material into lithium-rich manganese-based cathode material as described in claim 1, characterized in that, In step S5, the sintering temperature of the second step is 850℃-950℃, the holding time is 11h-13h, and the sintering atmosphere is an oxidizing atmosphere.
Citation Information
Patent Citations
Recycling method for anode material of ternary lithium battery
CN112063847A
Method for recycling battery-grade cobaltous oxide from ternary positive electrode material
CN114772654A